Pengaruh Kepemimpinan, Motivasi Kerja Dan Disiplin Kerja Terhadap Kinerja Karyawan Pada Pt. Kontak Perkasa Futures Makassar - Ady Andardinata; Nurhidayati Islamiyah; Wisda Zulaeha Suwardi; Nurlela (STIM-LPI Makassar, 2026)
The purpose of this study is to examine the influence of leadership, work motivation, and work discipline on employee performance at PT Kontak Perkasa Futures Makassar. The sampling method employed was a population sampling (census) approach, in which all 42 employees were selected as respondents. The study utilized both quantitative and qualitative data. Data collection methods included library research and field research. Data processing was conducted using SPSS version 26 to identify independent variables affecting the dependent variable. The data analysis techniques comprised descriptive analysis and statistical analysis, including multiple linear regression, correlation coefficient, coefficient of determination, t-test, and F-test to determine the significance of each variable’s effect. The results indicate that partially, leadership has a negative effect on employee performance, while work motivation and work discipline have a positive and significant effect on performance. Simultaneously, leadership, work motivation, and work discipline collectively have a positive and significant influence on employee performance.